Potensi Ekstrak Etanol Daun Lidah Buaya (Aloe vera L.) Sebagai Antifertilitas Melalui Tampilan Imunohistokimia Caspase 3 Aktif Pada Testis Serta Penilaian Kuantitas dan Kualitas Spermatozoa Mencit (Mus musculus L.) - Maria Lestari; M Pandapotan Nasution; Sry Suryani (Jurnal Pendidikan Kimia (JPKim), 2015)
Abstract. Control of male fertility is one of the  goverment efforts to reduce the number of population. Several researches have been done to make a male contraceptive, one of them is using herb to effect male reproductive system. Aloe vera (Aloe vera L.) has been widely cultivated by the people and used as materials for food and drugs. One of the benefits of this plant is it’s potential antifertility. For this research aims to test the antifertility potential of ethanol extract in Aloe vera (Aloe vera L.) leaf. in male mice (Mus musculus L.) DDW (Double Ditch Webster) strain. This is an  experimental research with complete randomization. Extract administered orally once a day for four weeks to of 24 male mice which divided into four groups: control group (0.5 ml/kgBW Aqudest), treatment group dosage 5mg/kgBW, 10mg/kgBW, 15mg/kgBW extract. We observed the expression of active caspase-3 microscopically through immunohistochemical appearance, quantity (number of spermatozoa) and quality (viability of sperm, sperm morphology and motility). The results were statistically analyzed using one-way ANOVA followed by multiple comparison (post hoc - Bonferroni test). The results showed between ethanol extract of Aloe vera leaf with the first dosage (5mg/kgBW), second dosage (10mg/kgBW) and the third dosage (15mg/kgBW) a significant reduction of the quantity and quality of spermatozoa (p <0.05). on the other hand activity of caspase 3 expression active has increased significantly (p<0.05) in spermatogonial cells of seminiferous tubules during the administration of ethanol extract of Aloe vera (Aloe vera L.) leaf. This shows an increase in the incidence of apoptosis during spermatogenesis. From these results it can be concluded that the ethanol extract of Aloe vera leaf has potency to be an antifertility drug that can later be developed for the manufacture of male contraception. Keywords: aloe vera extract, caspase-3, spermatozoa, quantity, quality